DESCRIPTION OF SERUM GAMMA GLUTAMYL TRANSFERASE LEVELS IN CONSUMERS OF TRADITIONAL ALCOHOLIC BEVERAGES IN GORONTALO CITY (Journal of Health, Technology and Science (JHTS), 2025)
Alcohol is an addictive and psychoactive substance that causes changes in the body's systems, both acute and chronic.  Alcohol abuse can cause various malfunctions in human organs, such as the liver and pancreas, and trigger cancer. Traditional alcoholic beverages can cause multiple health problems. This research method uses descriptive cross-sectional research, which is observational research with a quantitative approach. The population in this study consisted of people in Gorontalo who consumed traditional alcoholic beverages. The sample used was 15, and the sampling techniques used were purposive. The results obtained Gamma Glutamyl Transferaselevels of traditional alcoholic beverage consumers in Gorontalo city who have normal serum gamma-glutamyl transferase age category 10-18 amounted to 2 people (13.33%), age category 19-27 years amounted to 10 people (86.67%). Most of the respondents who made the research sample had a frequency of consumption of traditional alcoholic drinks per week 1 time as many as 10 people (66.67%) and a frequency of consumption of conventional alcoholic drinks per week 2-3 times as many as 5 people (33.33%). Most respondents who made the research sample consumed traditional alcoholic beverages for less than 5 years, totaling 11 people (73.33%), consuming traditional alcoholic drinks for less than 5 - 10 years, totaling 4 people (26.67%).